2017
DOI: 10.1002/jmv.24786
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic characteristics of HIV‐1 among travelers entering China from Myanmar: A retrospective study

Abstract: Due to the open policy of the Chinese government, a large number of Burmese individuals enter China at land ports in Yunnan province for travel or business. However, the situation of HIV-1 infection and its phylogenetic characteristics among these travelers remains unclear, which is a potential threat to public health. From January 2003 to December 2012, a total of 1,961 travelers were detected to be positive for HIV-1 infection at land ports between Myanmar and Yunnan province, China. From 1153 (58.8%) Burmes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Mobility behavior from the BSS data showed that 14.6% of PWID traveled to different districts while few traveled to India and bought sex while abroad (NASP, 2017). Nepal reported high HIV prevalence among returnees from India, particularly FSW (44%) (Zhang et al, 2017). In contrast, China reported a low HIV prevalence (0.2%-0.6%) among cross border travelers from Myanmar and Vietnam (Wang et al, 2017;Zhang et al, 2017).…”
Section: Discussionmentioning
confidence: 98%
“…Mobility behavior from the BSS data showed that 14.6% of PWID traveled to different districts while few traveled to India and bought sex while abroad (NASP, 2017). Nepal reported high HIV prevalence among returnees from India, particularly FSW (44%) (Zhang et al, 2017). In contrast, China reported a low HIV prevalence (0.2%-0.6%) among cross border travelers from Myanmar and Vietnam (Wang et al, 2017;Zhang et al, 2017).…”
Section: Discussionmentioning
confidence: 98%
“…The target fragment for the subgenotyping includes 99 amino acid coding codons from the protease (PR) region, and resistance analysis consists of approximately 300 amino acid coding codons from the reverse transcriptase region (primer sequences listed in Supplementary Table S1). The subgenotype of HIV-1 was tested using Bioedit and MEGA5 software with the standard strains selected from the Los Alamos HIV database, and mutation sites were identified using the Stanford HIV-resistant database (Rhee et al, 2017;Zhang et al, 2017).…”
Section: Subgenotype Determination and Drug Resistance Gene Mutation mentioning
confidence: 99%
“…To achieve the UNAIDS 90–90–90 goals, a series of harm reduction programs that focused on foreigners were performed by the Yunnan government [16]. From January 2003 to December 2012, the HIV status of over 70,000 foreigners entering Yunnan from Myanmar was detected, and 1961 were found to be HIV-1 seropositive [17]. Compared with those (e.g., businessmen and travelers) who crossed the border through land ports, transnational migrant IDUs more commonly went through convenient byways along the 2,185-kilometer border between China and Myanmar for the purpose of purchasing drugs, visiting family or friends, and/or doing business or odd jobs [18,19].…”
Section: Introductionmentioning
confidence: 99%